Adsorption of Arsenate on Iron Oxides as Influenced by Humic Acids. Issue 6 (1st November 2015) - Luo, Chang; Xie, Yawei; Li, Fang; Jiang, Tao; Wang, Qiang; Jiang, Zhenmao; Wei, Shiqiang
Abstract : Humic acid (HA) and iron oxides (FeOs) commonly coexist, and their interactions alter their ability to adsorb pollutants in the environment. The influences of HA on arsenate [As(V)] adsorption on FeOs were investigated on the preformation of complexes and their coexistence with As(V) in solution. The results indicated that HA could be strongly adsorbed on FeOs, and the adsorption capacity ( Q max, mg g −1 HA‐C) followed the sequence goethite (7.73) > ferrihydrite (3.14) > hematite (2.25) with a desorption rate <1%. The HA adsorbed existed uniformly on the FeOs surfaces in spot form and did not change the x‐ray diffraction (XRD) patterns of FeOs. The formation of FeOs‐HA complexes altered As(V) adsorption with a reduced adsorption capacity, prolonged reaction kinetics, and enhanced adsorption strength. The As(V) adsorption on both FeOs and FeOs‐HA complexes decreased with increasing pH (2.5–9) or decreasing ionic strength (0.2–0 M). The coexistence of HA in solution linearly decreased the As(V) adsorption on FeOs. Thus, our results demonstrated two impact pathways of HA on As(V) adsorption on FeOs: (i) blockage or occupation in the surface sites of FeOs if HA preformed complexes with FeOs and (ii) a competition to the surface sites of FeOs when HA coexisted with As(V) in the solution. Core Ideas: Iron oxides can strongly absorb humic acid with desorption rates <1%. The humic acid adsorbed existed uniformly on the iron oxide surfaces in fluffy spot forms. Humic acid reduced the adsorption capacity and kinetics of As(V) on iron oxides but enhanced the adsorption strength. Humic acid exerted its effect on As(V) adsorption by occupation or blockage of the surface adsorption sites. Complexation of humic acid with iron oxides did not change their patterns response to pH and ionic strength.